1989
DOI: 10.2337/diab.38.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brain in Counterregulation of Insulin-Induced Hypoglycemia in Dogs

Abstract: The role of the brain in directing counterregulation during hypoglycemia induced by insulin infusion was assessed in overnight-fasted conscious dogs. Concomitant brain and peripheral hypoglycemia was induced in one group of dogs (n = 5) by infusing insulin peripherally at a rate of 3.5 mU.kg-1.min-1. In another group (n = 4), insulin was infused as described above to induce peripheral hypoglycemia, and brain hypoglycemia was minimized by infusing glucose bilaterally into the carotid and vertebral arteries to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 0 publications
1
103
0
Order By: Relevance
“…Glucagon and sympathoadrenal activation is important in the early counter-regulatory responses to hypoglycaemia. On the other hand, cortisol and growth hormone responses, which occur after a prolonged and severe decrease in circulating glucose concentrations, are important for the long-term maintenance of blood glucose concentrations [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon and sympathoadrenal activation is important in the early counter-regulatory responses to hypoglycaemia. On the other hand, cortisol and growth hormone responses, which occur after a prolonged and severe decrease in circulating glucose concentrations, are important for the long-term maintenance of blood glucose concentrations [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, neural pathways stimulated by hypoglycemia induce feeding behavior [2]. Hormone responses and symptoms of hypoglycemia tend to be blunted in DM patients treated with insulin, and it is likely that deficient responses to hypoglycemia result from recurrent severe hypoglycemia sustained over many years of insulin replacement [1] CNS mechanisms of autonomic and endocrine responses to hypoglycemia have been studied in dogs and in rodents, and these studies indicate participation of structures in brainstem as well as hypothalamus [3][4][5][6][7][8][9][10][11][12]. Although these animal studies have proven useful in elucidating aspects of neural circuitry underlying counterregulatory hormone secretion, symptom thresholds, per se, cannot be directly assessed in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the major mammalian hypoglycaemia sensor has been considered to be within the brain, particularly including the hypothalamus. The evidence for this includes the inhibition of neuroendocrine counterregulatory responses to systemic hypoglycaemia when brain glucose concentrations are maintained by selective glucose infusion [8,9]; the development of hyperglycaemia after hypothalamic lesions [10]; the induction of a counterregulatory response in euglycaemic animals by localised glucoprivation in the ventromedial hypothalamus [11] and the amelioration of counterregulatory responses to acute hypoglycaemia in animals when hypothalamic glucose concentrations are sustained by microdialysis of glucose solutions into the area [12]. However, the primacy of the cranial hypoglycaemia sensor has been challenged by studies showing similar suppression of counterregulatory responses to acute hypoglycaemia when portal vein and hepatic glucose concentrations are sustained by local infusion in rats and dogs [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Selective catheterisation studies in dogs showed a reduction in the counterregulatory hormone responses to systemic hypoglycaemia when brain glucose concentrations were maintained artificially, suggesting that the hypoglycaemia sensor is in the brain [8,9]. More recent studies using microdialysis catheters in rats localised the glucose sensor to the ventromedial nuclei of the hypothalamus (VMH) [10,11,12,13].…”
mentioning
confidence: 99%